Conhecimento dos presidiários sobre as DST/HIV e AIDS e medidas de prevenção num sistema penitenciário - França, Ana C.N (Brazilian Journal of Sexually Transmitted Diseases, 2000)
The study pilot had as objcctiveto verify the prisoners knowledge on DST/HIV and Sida ond the prevention measures. in a Penitentiary System of Rio Branco - Acre - Brazil. The results show a young, single populotion and with less than a year of prison. The diseases more memioned by them they went to gonorrhea. HIV syphilis and hepatitis. where it stands out the bass use of preservatives in its sexual practices. The prisoners liked this experience, was motivated, stímulated and until they would like to particípate in imemal campaigns of prevention, close to a programs of university extension.